Review of potential improvements using MRI in the radiotherapy workflow - Torresin, Alberto; Brockmann, Marc Alexander; Schad, Lothar R.; Attenberger, Ulrike; Lohr, Frank (Zeitschrift für medizinische Physik, 2015)
The goal of modern radiotherapy is to deliver a lethal amount of dose to tissue volumes that contain a significant amount of tumour cells while sparing surrounding unaffected or healthy tissue. Online image guided radiotherapy with stereotactic ultrasound, fiducial-based planar X-ray imaging or helical/conebeam CT has dramatically improved the precision of radiotherapy, with moving targets still posing some methodical problems regarding positioning. Therefore, requirements for precise target delineation and identification of functional body structures to be spared by high doses become more evident. The identification of areas of relatively radioresistant cells or areas of high tumor cell density is currently under development. This review outlines the state of the art of MRI integration into treatment planning and its importance in follow up and the quantification of biological effects. Finally the current state of the art of online imaging for patient positioning will be outlined and indications will be given what the potential of integrated radiotherapy/online MRI systems is.
Gesehen am 05.07.2017